2008
DOI: 10.21314/jor.2008.174
|View full text |Cite
|
Sign up to set email alerts
|

Value-at-risk and extreme value distributions for financial returns

Abstract: The ability of the Generalised Extreme Value (GEV) and Generalised Logistic (GL) distributions to fit extreme financial returns in the stock, commodities and bond markets is assessed. The empirical results indicate that the too much celebrated GEV is not the most appropriate model for the data since the fatter tailed GL is found to provide better descriptions of the extreme returns. Extreme Value Theory (EVT) based VaR estimates are then derived and compared to those generated by traditional methods. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 51 publications
5
24
0
Order By: Relevance
“…Moreover, the three models can be considered as the limit distribution of extremes in different situations. These results justify the theoretical importance of the empirical findings, that GL can be a suitable model over GEV model for extremes of share market data, see for example [1, 25,26]. Many papers also show that GL distribution provides an adequate distribution in hydrological application, for eg.…”
Section: Goodness Of Fit Test For the Bse Datasupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, the three models can be considered as the limit distribution of extremes in different situations. These results justify the theoretical importance of the empirical findings, that GL can be a suitable model over GEV model for extremes of share market data, see for example [1, 25,26]. Many papers also show that GL distribution provides an adequate distribution in hydrological application, for eg.…”
Section: Goodness Of Fit Test For the Bse Datasupporting
confidence: 57%
“…[1, 23,24] etc. Also [25] empirically showed that GL is better than GEV to model extreme movements in the stock, commodities and bond markets.…”
Section: Definition 14 a Random Variable X Is Said To Follow The Genmentioning
confidence: 99%
“…[8] Concluded that the GP is the better model as there is less wasting of data. However, [9] states that although the GP distribution does have its advantages over the GEV, it is subjected to more serial dependence. [9] Therefore applied a non-overlapping sub period technique to the financial data to reduce dependency.…”
Section: Introductionmentioning
confidence: 99%
“…However, [9] states that although the GP distribution does have its advantages over the GEV, it is subjected to more serial dependence. [9] Therefore applied a non-overlapping sub period technique to the financial data to reduce dependency. He then fit the Generalized Logistic (GL) distribution and the GEV to the data and compared the results to determine which model better describes the extreme events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation